Reaction of porphyrin-based surface-anchored metal?organic frameworks caused by prolonged illumination - Senge, Mathias (My University, 2018)
Crystalline surface-anchored metal–organic framework (SURMOF) thin films made from porphyrin-based organic linkers have recently been used in both photon upconversion and photovoltaic applications. While these studies showed promising results, the question of photostability in this organic–inorganic hybrid material has to be investigated before applications can be considered. Here, we combine steady-state photoluminescence, transient absorption, and time-resolved electron paramagnetic resonance spectroscopy to examine the effects of prolonged illumination on a palladium-porphyrin based SURMOF thin film. We find that phototreatment leads to a change in the material's photoresponse caused by the creation of stable products of photodecomposition – likely chlorin – inside the SURMOF structure. When the mobile triplet excitons encounter such a defect site, a short-lived (80 ns) cation–anion radical pair can be formed by electron transfer, wherein the charges are localized at a porphyrin and the photoproduct site, respectively.
PUBLISHED
Keywords: Surface-anchored metal-organic framework (SURMOF); Thin films; Porphyrins